Measuring illicit financial flows: A gravity model approach to estimate international trade misinvoicing - Lourenço Senne Paz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Illicit financial flows have recently attracted the attention of academia, practitioners, and multilateral organizations who consider them harmful to economic development. Some observers suggest that many of these flows occur via the misinvoicing of international trade transactions. This study develops a novel methodology based on the gravity model of international trade to estimate illicit financial flows using publicly available product-level international trade data. It contributes to the literature by estimating product-level transportation and insurance costs and providing, for the first time, an estimation for all countries of an upper bound of the values of export and of import over- and under-misinvoicing separately, without resorting to assumptions about trade statistics reliability. Application of the methodology is illustrated using six-digit product-level UN Comtrade data for 2013-16. The results indicate that misinvoicing is not confined to a few products or countries but is a widespread phenomenon that deserves future research.
Keywords: C23; F14; F24; O17; 330; gravity model; illicit financial flows; international trade; misinvoicing; transportation and insurance cost